A new technology for rice straw pelleting in Vietnam - CGIAR Research Program on Rice (2019)
A techno-economic investigation of rice straw densification to produce pellets, to be used for animal feed. The study also looked into the quality of the product in terms of uptake and digestibility of the cattle feed.